"The Impact of the Internal Control System on Reducing Financial and Administrative Corruption in Insurance Companies (A Field Study on Insurance Companies Operating in the City of Benghazi)" (Comprehensive Journal of Science, 2025)
This study aims to investigate the impact of the internal auditing system in reducing financial and administrative corruption in insurance companies. To achieve the objectives of the study, the descriptive-analytical method was adopted, addressing the concept of internal auditing, financial corruption, and administrative corruption. Concerning the practical aspect, a questionnaire was designed to study the variables and distributed to 83 employees from public and private insurance companies in Benghazi, as a primary source of data collection related to the study topic. The data were coded, analyzed, and processed using the statistical program (SPSS) and appropriate statistical tools. The study concluded that the internal auditing system plays a significant role in reducing financial and administrative corruption in insurance companies in Benghazi. The findings indicate that the effectiveness of the internal auditing system largely depends on the support provided by top management, as such support enhances its importance and enables it to control and combat financial and administrative corruption effectively.
Keywords: Internal ,Auditing System, Financial and, Administrative, Corruption.